A cross-sectional study on social anxiety disorder and self- esteem among undergraduate medical students of a tertiary health care centre in central India - George, Anju; Jadhao, Ashok R.; Agrawal, Sanjay; Mathew, Ebin; M., Kalaivani (International Journal Of Community Medicine And Public Health, 2024)
Background: Social anxiety disorder (SAD) aka social phobia is a persistent fear of one or more social situations where embarrassment may occur and the fear or anxiety is out of proportion to the actual threat posed by the social situation as determined by the cultural norms. Self-esteem is an attitude or a sense of worth as a person. People low in self-esteem are generally more dependent on others and more susceptible to external cues that carry self-relevant implication. This study aims to estimate the prevalence of Social anxiety disorder and to assess the status of self-esteem and to determine the association of SAD with self-esteem among undergraduate medical students. Methods: A cross-sectional study was conducted among 382 undergraduate medical students and interns of a tertiary health care institute. Social phobia was assessed using Social-phobia-Inventory (SPIN) questionnaire and self-esteem using Rosenberg self-esteem scale. Results: Among 382 study participants, 180 (47.1%) were females and 202 (52.9%) were males. 203 (53.1%) had social anxiety disorder. 135 (35.3%) students had low self-esteem. There was a statistically significant association between social phobia and status of self-esteem. Conclusions: This study showed that a higher proportion of medical students had social anxiety disorder and 35.3% had low self-esteem. So, early detection and appropriate intervention need to be done among the students to improve self-esteem and to enhance social interaction by their institutes.